2013
DOI: 10.1111/iej.12164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of zinc oxide nanocrystals and histologic evaluation of their biocompatibility by means of intraosseous implants

Abstract: ZnO nanocrystals were biocompatible, well tolerated and allowed new bone formation and bone remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…5a). Similar fi ndings were informed by Augustine in wound skin healing model 53) and by Sousa in wound bone healing 54) . Also, the presence of infl ammatory cells and new vascular formation surrounding ZnO particles (Table 1) an unresolved infl ammation could be related to the dissolution of ZnO and hence ROS generation.…”
Section: Discussionsupporting
confidence: 55%
“…5a). Similar fi ndings were informed by Augustine in wound skin healing model 53) and by Sousa in wound bone healing 54) . Also, the presence of infl ammatory cells and new vascular formation surrounding ZnO particles (Table 1) an unresolved infl ammation could be related to the dissolution of ZnO and hence ROS generation.…”
Section: Discussionsupporting
confidence: 55%
“…Here, the X-ray diffractogram and micro-Raman spectrum confirmed that the synthesis methodology employed produced pure, homogeneous and uncontaminated ZnO NPs, in hexagonal wurtzite (Wz) structures, with an average size of 20 nm. This methodology has been widely used and provides the best control over properties such as dimension, structure, purity and stability that are fundamental in biological assays (Song et al, 2010;Sousa et al, 2014). They suggested a 24 h exposure to be ample to determine genotoxic response; advised that the genotoxicity studies consider in parallel complete and reduced serum content in media and M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…ZnO NPs (average size of 20 nm) were synthesised by coprecipitation (Dantas et al, 2008a;Dantas et al, 2008b;Sousa et al, 2014). The reaction was complete after four hours and yielded a ZnO precipitate that was collected, centrifuged and washed five times, first with M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT diffractogram (XRD) was acquired using an XRD-6000 (Shimadzu) with monochromatic CuKa1 (λ = 1.54056 Å) radiation.…”
Section: Synthesis and Characterisation Of Zno Npsmentioning
confidence: 99%
“…Several types of nanocrystals have been synthesized in order to obtain an efficient nanomaterial. However, it is important to emphasize that nanocrystals must be biocompatible and specific [45]. Based on this and knowing that zinc oxide nanocrystals (ZnO) are biocompatible materials, according to the US Food and Drug Administration (FDA), in this chapter we investigated this nanocrystal.…”
Section: Doped Semiconductors Nanocrystals and Nanocompositesmentioning
confidence: 99%